2019
DOI: 10.3390/su11174687
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Application of the UNIDO Eco-Industrial Park Toolbox in Viet Nam and Other Countries

Abstract: The transformation of conventional industrial parks into eco-industrial parks (EIPs) presents an effective opportunity to attain inclusive and sustainable industrial development. UNIDO has acquired broad experience of EIPs by implementing a number of EIP projects in developing countries. To support these, a UNIDO EIP Toolbox was developed in order to (a) provide a practical set of customized and flexible tools to assist practitioners with the development and implementation of EIPs and related initiatives, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…van Beers et al. (2019) applied the EIP framework in Vietnam and other countries, including Colombia, Morocco, and South Africa, where they argue for the tool to be improved and the implementing country to achieve their standards. China also carried out a comparative analysis of its standards against the international framework (The World Bank, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…van Beers et al. (2019) applied the EIP framework in Vietnam and other countries, including Colombia, Morocco, and South Africa, where they argue for the tool to be improved and the implementing country to achieve their standards. China also carried out a comparative analysis of its standards against the international framework (The World Bank, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The IF‐EIP framework encourages industrial parks to exceed compliance and go beyond the defined standards to fit the region. The application of the framework has shown its importance in contributing to the implementation of EIP practices and supporting the stakeholders in making decisions related to EIP topics (van Beers et al., 2019).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…An overview of existing tools related to EIPs is provided in an earlier publication by UNIDO [33]. This review of existing tools (e.g., [34][35][36][37]) showed that a limited number of practical tools customized to the development and implementation of EIPs are freely available.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…UNIDO's EIP Toolbox is available from: https://greenindustryplatform.org/GEIPP. Lessons learned from the application of the UNIDO EIP Toolbox are detailed in [33].…”
Section: Unido's Eip Assessment Toolmentioning
confidence: 99%
See 1 more Smart Citation